2020
DOI: 10.1159/000507122
|View full text |Cite
|
Sign up to set email alerts
|

Does Smoking Cessation at Primary Diagnosis Reduce the Recurrence Risk of Nonmuscle-Invasive Bladder Cancer? Results of a Prospective Study

Abstract: Introduction: Evidence that smoking cessation at first diagnosis of nonmuscle-invasive bladder cancer (NMIBC) reduces the risk of recurrence is lacking. The aim of our prospective study was to analyze the association between patients' changes in smoking habits after diagnosis and recurrencefree survival (RFS). Patients: After transurethral resection of primary NMIBC, patients were classified as "ex-smokers," i.e., those definitively stopping, and as "active smokers," i.e., those continuing or restarting to smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 23 publications
(25 reference statements)
1
13
0
2
Order By: Relevance
“…Only nine articles were finally found eligible and included in the systematic review [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]: these were published between 1999 and 2021 and encompassed a total of 5490 BC patients (ranging across studies from a minimum of 107 to a maximum of 1733) ( Table 1 ). All studies’ mean/median age at BC diagnosis fell in the seventh or eighth decade of life.…”
Section: Resultsmentioning
confidence: 99%
“…Only nine articles were finally found eligible and included in the systematic review [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]: these were published between 1999 and 2021 and encompassed a total of 5490 BC patients (ranging across studies from a minimum of 107 to a maximum of 1733) ( Table 1 ). All studies’ mean/median age at BC diagnosis fell in the seventh or eighth decade of life.…”
Section: Resultsmentioning
confidence: 99%
“…Somit stellt die entsprechende Aufklärung der Patienten mit neu diagnostiziertem BCa einen durchaus relevanten Punkt in der Behandlung dar. Die Risikoreduktion für ein Tumorrezidiv bei nichtmuskelinvasivem BCa nach ≥ 15 Jahren Rauchstopp ist signifikant [40]. Trotzdem schaffen es nur ungefähr 35 % der Raucher, nach der Diagnose eines BCa im Verlauf den Nikotinkonsum definitiv zu sistieren [40].…”
Section: Rauchentwöhnungunclassified
“…Die Risikoreduktion für ein Tumorrezidiv bei nichtmuskelinvasivem BCa nach ≥ 15 Jahren Rauchstopp ist signifikant [40]. Trotzdem schaffen es nur ungefähr 35 % der Raucher, nach der Diagnose eines BCa im Verlauf den Nikotinkonsum definitiv zu sistieren [40]. Die Wichtigkeit und Effektivität der ärztlichen Beratung im Zusammenhang mit dem Nikotinabusus und die Anbindung der Patienten an ein Rauchentwöhnungsprogramm wird unterschätzt.…”
Section: Rauchentwöhnungunclassified
“…9–11 Initial retrospective studies that examined the association between post-diagnosis smoking exposure and recurrence risk concluded that quitting smoking might reduce recurrence risk 12,13 but more recent, prospective studies did not confirm this association. 14,15…”
mentioning
confidence: 99%
“…9e11 Initial retrospective studies that examined the association between postdiagnosis smoking exposure and recurrence risk concluded that quitting smoking might reduce recurrence risk 12,13 but more recent, prospective studies did not confirm this association. 14,15 To our knowledge, all prior studies on smoking and NMIBC recurrence risk have relied on self-reported smoking exposure assessments. We recently reported that biochemical verification of cotinine in urine or saliva specimens can more accurately identify patients who are actively smoking than relying on self-report.…”
mentioning
confidence: 99%